COMPARISON OF ANTIMONY BEHAVIOR WITH ARSENIC UNDER VARIOUS SOIL REDOX CONDITIONS - Mitsunobu S.; Harada T.; Takahashi Y. (My University, 2006)
The municipal solid waste (MSW) landfills are the significant sources of atmospheric contamination, due to biogas production by anaerobic decomposition of organic matter via bacterial activity. Biogas released from landfills is commonly composed of a mixture of methane (55%-60%) and carbon dioxide (40%-45%), with minor contents of N2, H2, CO and traces of toxic and bad smelling inorganic and organic compounds.
Keywords: ANTIMONY; ARSENIC; XAFS; HPLC-ICP-MS; REDOX CONDITION